Investigation on Microstructure, Hardness, Wear behavior and Fracture Surface Analysis of Strontium (Sr) and Calcium (Ca) Content A357 Modified Alloy by Statistical Technique (Fracture and Structural Integrity, 2023)
The aluminum alloy are extensively used in several industrial applications. Stir casting is one of the most frequently accepted methods. In the present investigation, how the microstructure, mechanical and wear mechanics of A357 alloy were impacted by the presence of Sr/Ca was investigated. The outcomes revealed that addition of elements (Sr/Ca) enhance the microstructural features. Uniform dispersal of particulates (Sr/ Ca) in Al357 alloy and also the modified structure of silicon (Si) were observed. Hardness of modified alloy was evaluated by using hardness tester. A result reveals that hardness of modified alloy was improved by increasing in the Sr/Ca content. The wear rate of modified alloy was evaluated by using Pin and Disc wear test rig. Test trials were conducted according to Taguchi technique. L27 array was implemented for evaluation of data. The effect of varying parameters (factors) on wear loss and COF were analyzed using ANOVA (Analysis of Variance) method. ANOVA outcomes shown that, the Sr/Ca content has a better significant impact on wear behavior and COF of the modified alloy. A wear fractography result shows the internal fracture structure of a wornout surface which was studied by SEM analysis.
Keywords: A357 Alloy; Strontium (Sr); Calcium (Ca); Stir casting; Hardness; Wear behavior; Fracture surface; Statistical technique